2017
DOI: 10.1292/jvms.16-0593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diagnosis and treatment of clinical endometritis based on vaginal discharge score grading system in postpartum Holstein cows

Abstract: In this study, the prevalence, effectiveness of diagnosis, and treatment based on vaginal discharge score (VDS) of clinical endometritis in cattle were evaluated. To detect clinical endometritis and classify its severity, vaginoscopy was performed during 21 to 60 days postpartum in 164 Holstein cows consisting of 229 lactations. Groups were defined using the 4-point VDS scale. Study groups included the following: non-endometritis (VDS=0; no/clear mucus; NEM group; n=168); mild endometritis, no treatment (VDS=1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 21 publications
(75 reference statements)
3
27
1
Order By: Relevance
“…Therefore, further studies are needed to confirm the effect of CM diagnosed between different time periods after calving on fertility. In agreement with the findings of a recent study (Okawa et al, 2017), CEM occurring between 22 and 28 DIM and treated with intrauterine antibiotics also had a significant positive effect on the days open.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, further studies are needed to confirm the effect of CM diagnosed between different time periods after calving on fertility. In agreement with the findings of a recent study (Okawa et al, 2017), CEM occurring between 22 and 28 DIM and treated with intrauterine antibiotics also had a significant positive effect on the days open.…”
Section: Discussionsupporting
confidence: 92%
“…The threshold values of PMN for predicting SCLE positive case are 8% PMN for 21 to 33 DIM; 6% PMN for 34 to 47 DIM; and 4% PMN for 48 to 60 DIM. However, the PMN threshold for the overall period (21 to 62 DIM) is ≥5% when the applied method counts 300 cells per endometrial cytology slide ( Madoz et al., 2013 ; Melcher et al., 2014 ; Okawa et al., 2017 ; Chan Lee et al., 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The former is commonly and extensively used with different veterinary drugs (VD). These VD include antimicrobials (Ceftiofur hydrochloride, oxytetracycline, procaine penicillin G and dihydrostreptomycin, gentamicin, tetracycline hydrochloride and cephapirin) ( Bartolome, Khalloub, de la Sota, Drillich & Melendez, 2014 ; Kasimanickam et al., 2005 ; Okawa et al., 2017 ; Pierre, 2010 , Kumar & Purohit, 2019 , Manimaran et al., 2019 ), non-steroidal anti-inflammatory drug (Phenylbutazone) ( Tek et al., 2010 ); and hormones (Prostaglandins) ( Ahmadi, Mogheiseh, Mirzaei, Nazifi & Fallah, 2018 ; Makki, Ahmadi, Gheisari & Nazifi, 2017 ). In the latter, different phytotherapeutic agents used include Tinosporacordifolia, Withaniasomnifera, Curcuma longa, Ocimum sanctum, Allium sativum, and Azadirachtaindica ( Mandhwani et al., 2017 ; Bakare et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Along with this, pathology of the endometrium usually affects cows, which acquires subclinical mastitis in the 1 st day after calving. Studies have shown that 37.3% of cows in the postpartum period are affected by both mastitis and endometritis and, in 54% of cases, by purulent-catarrhal form [ 14 ], which is directly related to pathogenic and opportunistic microflora [ 15 - 21 ]. It should be noted that subclinical endometritis develops in case of untimely diagnosis or unskilled care, which is one of the most significant causes for reproductive system disorders in cattle breeding [ 22 - 28 ].…”
Section: Introductionmentioning
confidence: 99%